Analisis Pengalaman Wisatawan Berdasarkan Visitor Journey Di Kampung Ekowisata Keranggan, Tangerang - Kevlin Ariansyah; Wiwik Sari (Journal of Innovation Research and Knowledge, 2026)
This study examines tourists’ experiences across each stage of the visitor journey at Keranggan Ecotourism Village. The village is a community-based tourism destination that was recognized among Indonesia’s Top 75 Tourism Villages in the 2023 Indonesian Tourism Village Award (ADWI). The research was motivated by a research gap identified in previous studies, which primarily focused on promotion and destination management from the perspective of destination managers, while tourists’ experiences have received limited attention. This study employed a qualitative approach, using observation, interviews, and documentation as data collection techniques. The informants consisted of five tourists and two destination managers selected through purposive sampling, and the data were analyzed using the Miles and Huberman model. The findings indicate that during the pre-visit stage, tourists obtained information through Instagram, Google Maps, and recommendations from friends; however, they experienced limitations in accessing information regarding available activities and visitation procedures. During the during-visit stage, tourists appreciated the natural environment, tranquil atmosphere, and interactions with local residents, although challenges related to limited information and supporting facilities were still encountered. In the post-visit stage, tourists generally expressed satisfaction with their overall experience; however, some were hesitant to revisit due to accessibility constraints and the quality of certain facilities. The study also identified a gap between digital promotional content and the actual conditions of the destination. Therefore, destination promotion should focus on providing clearer and more accurate information that reflects the actual experiences of visitors